Multiagent system technologies 9th German Conference, MATES 2011, Berlin, Germany, October 6-7, 2011. Proceedings - MATES 2011 (2011 Berlin, Germany); Klügl, Franziska; Ossowski, Sascha; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the proceedings of the 9th German Conference on Multiagent System Technologies held in Berlin, Germany, in October 2011. The 12 revised full papers presented together with 6 short parers were carefully reviewed and selected from 50 submissions. Providing an interdisciplinary forum for researchers, users, and developers to present and discuss latest advances in research work as well as prototyped or fielded systems of intelligent agents and multi-agent systems, the papers cover the whole range of this sector and promote its theory and applications.
Electronic reproduction.
Keywords: Multiagent systems -- Congresses; Computer science; Electronic books